Vaccination coverage of patients with type 2 diabetes mellitus: Challenging issues from an outpatient secondary care setting in Greece - Galanos, Georgios; Dimitriou, Helen; Pappas, Angelos; Perdikogianni, Chrysoula; Symvoulakis, Emmanouil K.; Galanakis, Emmanouil; Lionis, Christos (Frontiers in Public Health, 2022)
Background Increased morbidity/mortality due to vaccine preventable diseases (VPD) is encountered in type 2 diabetes (T2D) people. Aim of this study was to assess their vaccination coverage and describe trends possibly affecting compliance. Methods. Information on vaccination coverage was retrieved from either from documents or interview provided by patients, and/or their vaccination record card at a specialized outpatient diabetes center. The selection of the patients was arbitrary. Results An increasing vaccination rate for influenza was observed from 2018 to 2020 among 372 participants. The vaccination coverage for S.pneumoniae was 67.2% (PCV13), 20.4% (PPSV23), 26.3% for herpes zoster in individuals ≥60 years, 1.9% for tetanus-diphtheria-pertussis and 1.1% for hepatitis-B. A 10.2% of participants were found to be unvaccinated. Vaccination uptake for influenza and PCV13 was related to age, ≥3 comorbidities and long-term follow-up. T2D individuals consecutively vaccinated for influenza were 3.78 times more likely to be also vaccinated with PCV13. Conclusions Vaccination rates of patients with T2D show an increasing trend, especially for influenza and S. pneumoniae, although the one for S. pneumoniae was low. Older people seem more prone to vaccination, the one for herpes zoster was low with infected patients remaining unvaccinated while significantly low coverage was observed for other VPDs. The findings are important to improve effectiveness of preventative services.